1992
DOI: 10.2134/agronj1992.00021962008400020021x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Early Season Cotton Growth and Development

Abstract: Temperature is a primary environmental factor controlling growth and developmental rates of plants, yet little specific information is available regarding cotton (Gossypium hirsutum L.) responses to temperature. Information covering a wide range of temperatures would be useful for predicting both developmental and growth rates in cotton. Therefore, an experiment was conducted in naturally lit, temperature-and CO,-controUed cabinets from soon after emergence until 56 d after emergence (DAE). The cabinets were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 12 publications
12
71
0
1
Order By: Relevance
“…Many studies reported separately on changes in growth and physiology of cotton genotypes under drought stress (Pace et al 1999, Ullah et al 2008 and heat stress (Reddy et al 1992). However, these stress factors often accompany each other and occasionally appear alone.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported separately on changes in growth and physiology of cotton genotypes under drought stress (Pace et al 1999, Ullah et al 2008 and heat stress (Reddy et al 1992). However, these stress factors often accompany each other and occasionally appear alone.…”
Section: Resultsmentioning
confidence: 99%
“…Others attributed that production of the toxin is influenced by plant age or reproductive stage, and/or by a variety of environmental factors (Benedict et al, 1993;Wu et al, 1997). High temperature is one of the environmental factors to affect cotton development process (Reddy et al, 1992(Reddy et al, , 1998, the maximum temperature is usually at 36-40 • C, the period of high temperature occur for 6-10 days during cotton growing season in China (Miao et al, 1998;Zhou, 1999), and resulted in senescence of leaves, abscission of bolls and reduced lint yield (Zhou et al, 1996). The field investigation discovered that the reduction of the insect-resistant efficacy for Bt cotton was after high temperature climate.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural practices such as earlier planting to enhance yield, will undoubtedly evolve, but this will be limited by available radiation in non-summer periods. Many of the Upland cultivars do not tolerate the high temperatures projected, and the modern Pima cultivars are even more sensitive (Kittock et al 1981, 1988, Reddy et al 1992a,b, 1998b. As a result, strategies for reducing the impacts of climate change on cotton production should focus on developing heat-andcold-and drought-resistant cotton cultivars in order to mitigate the effects of climate change.…”
Section: Discussionmentioning
confidence: 99%